FINDTHON: Game-based Python Learning For PT3 Students - Ahmad Affendy, Ahmad Haziq Aiman; Saman, Fadhlina Izzah; Zainon, Nur Fatin Izzatie (2020)
Python language has emerged as one of the most widely used programming nowadays. However, from previous researches and survey that has been conducted, it is found that someof the techniques on teaching Python programming language in school nowadays are not quitehelpful and effective. Because of that, a game-based learning application is suitable to makethe learning of Python programming language more engaging and fun to the students. Thereare several problems that leads to the idea of this project which includes, learning Python using traditional methods is not effective and not enough time to learn Python in class, also students in general had difficulty recalling Python syntaxes. The Game Development Life Cycle(GDLC) model is used as the development methodology where it includes six phases namelythe Initiation phase, Pre-production, Production, Testing, Beta and Release phase. Game BasedLearning (GBL) model is implemented in the design and development process to ensure thegame developed has elements of learning and later can be used as a tool for learning Phyton.This application was built on mobile platform for Android that is the most widely usedoperating system and has open source feature which provides ubiquitous learning to the user.At the end of the project, the Game Based Learning application has been successfully developed. However, it can be further improved by adding features such as introducingmultilingual function, adding scoreboard for keeping track of high scores and allowingmultiplayer session for more enjoyable game and learning experience for students.